The role of internal control and corporate management: the case of a mining company in Peru - Valdivia Holguin, Ximena Rocio (2024)
Peru is a country that stands out for its important mining sector; therefore, the following study analyzes the relationship between internal control and business management within a mining company in the country. The methodology considers the basic type, descriptive-correlational level, and cross-sectional design, the universe being 379 workers of the mining company analyzed and the sample is made up of 178 workers. The research instruments used to obtain data and measure research variables are questionnaires and content analysis. The results revealed a significant relationship between internal control and corporate governance. Therefore, it can be concluded that the company lacks strength with regards to internal control culture. It is therefore recommended that training and awareness programs be implemented to strengthen internal control culture, so that employees may understand the importance of their role in business management, and the effective implementation of these controls.